2018
DOI: 10.3389/fmicb.2018.02243
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Escherichia coli Into a VBNC State by Continuous-Flow UVC and Subsequent Changes in Metabolic Activity at the Single-Cell Level

Abstract: A viable but non-culturable (VBNC) state of bacteria induced by disinfection in water treatment poses serious health risks because of possible resuscitation of VBNC cells during transportation. In this study, a setup using continuous-flow ultraviolet (UVC) irradiation ranging from 0 to 172.2 mJ cm-2 was designed to simulate real-world disinfection in both drinking water (SDW) and reclaimed water (SRW) treatment plants. A systematic investigation of UVC-induced VBNC bacteria, including occurrence, resuscitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Traditionally, enumeration of LBPs has relied on agar plating techniques to determine Colony Forming Units (CFU) 10 , and while this methodology remains a staple for the field, it may not be the most appropriate metric for all live bacterial therapeutics. For example, cells in a viable but nonculturable (VBNC) state may be unable to divide and form colonies but may nonetheless retain sufficient metabolic activity to perform some engineered functions in situ 87 . In this case, assessment of viability using commercial live/dead stains to detect intact cell membranes may be more appropriate for enumerating cells in the drug product 88 .…”
Section: Manufacturability Of Engineered Live Bacterial Therapeuticsmentioning
confidence: 99%
“…Traditionally, enumeration of LBPs has relied on agar plating techniques to determine Colony Forming Units (CFU) 10 , and while this methodology remains a staple for the field, it may not be the most appropriate metric for all live bacterial therapeutics. For example, cells in a viable but nonculturable (VBNC) state may be unable to divide and form colonies but may nonetheless retain sufficient metabolic activity to perform some engineered functions in situ 87 . In this case, assessment of viability using commercial live/dead stains to detect intact cell membranes may be more appropriate for enumerating cells in the drug product 88 .…”
Section: Manufacturability Of Engineered Live Bacterial Therapeuticsmentioning
confidence: 99%
“…These cells were identified by Xu et al, which showed that these bacterial cells could not grow on routine or selective media [168]. Moreover, VBNC cells were discriminated from dead cells, since they were similar to live cells, containing an intact membrane, an active mRNA transcription, metabolic activity, and respiration [169,170]. At least eighty-five bacterial species have been shown to enter a VBNC state, including foodborne and clinical pathogens [171].…”
Section: Bacterial Cells Dormant Phenotypes: a Tolerance Mechanismmentioning
confidence: 99%
“…Bacteria in the VBNC state still have active respiration. CTC can be reduced by electron transport chains to give off red fluorescence whose intensity reflects the number of viable cells ( Zhang et al, 2018 ). CTC solution was added to 500 μL of R. biphenylivorans TG9 at a final CTC concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%